2017
DOI: 10.1111/scd.12214
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Salivary Cortisol and α‐amylase Levels and Psychological Profiles in Patients with Burning Mouth Syndrome

Abstract: The results showed higher salivary levels of cortisol and α-amylase in patients with BMS compared to healthy individuals. Psychological problem was prevalent in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 24 publications
2
54
0
1
Order By: Relevance
“…Additionally, previous studies have shown controversial results regarding the salivary cortisol levels in BMS patients. Amenábar et al (3) and Kim et al (7) have shown elevated cortisol levels in BMS patients, which is in disagreement with Nosratzehi et al (8) and de Souza et al (9).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, previous studies have shown controversial results regarding the salivary cortisol levels in BMS patients. Amenábar et al (3) and Kim et al (7) have shown elevated cortisol levels in BMS patients, which is in disagreement with Nosratzehi et al (8) and de Souza et al (9).…”
Section: Discussionmentioning
confidence: 90%
“…Results from the literature point out that cortisol levels in saliva are increased in BMS patients as indicator of stress conditions (3,7). However, Nosratzehi et al (8) and de Souza et al (9) have shown that differences between salivary cortisol levels among BMS patients and control were not significant.…”
Section: Introductionmentioning
confidence: 98%
“…The contribution from oxidative stress must also be considered, given that stress‐related hormonal alterations in postmenopausal BMS patients may affect MUC1 expression and burning pain perception (Kang et al, 2017). Stress may, in fact, play a relevant role on BMS pathophysiology, because the stress‐related enzyme α‐amylase is also upregulated in saliva from BMS patients (Imura et al, 2016; Nosratzehi et al, 2017). Reports suggesting altered levels of reactive oxygen species (ROS) in saliva (Tvarijonaviciute, Aznar‐Cayuela, Rubio, Ceron, & Lopez‐Jornet, 2017), in addition to alterations in total oxidant capacity and biological antioxidant potential as iron‐reducing activity in blood (Tatullo et al, 2012) of BMS patients, support the contribution of oxidative stress to BMS pathogenesis.…”
Section: Pathophysiology Of Bmsmentioning
confidence: 99%
“…Due to the psychosomatic profile of this aetiology of this disease, stress-related proteins (such as cortisol and α -amylase) have been related to its presentation [ 122 , 123 ]. There are few studies investigating the role of salivary Igs in this pathology, and the existing ones have contradictory results.…”
Section: The Salivary Proteome In the Health-illness Spectrummentioning
confidence: 99%